The Impact of Covid-19 on the Financial Stability Evidence from Private Commercial Banks in Ethiopia: Dynamic Panel Data Analysis - Tsegaye, Adane Tilahun (International Journal of Economics and Financial Issues, 2025)
This study used the Generalized Method of Moments (GMM), a dynamic two-step approach, to examine the effect of COVID-19 on the financial stability of private commercial banks in Ethiopia. The study offered a thorough evaluation of the ways in which different elements affected financial stability during the pandemic period by examining data from 16 private banks. The results showed that the financial stability of the banks was positively impacted by COVID-19, the financial stability of the prior year, liquidity, and GDP. In particular, the financial climate has become more stable as a result of the pandemic-induced changes to digital banking and regulatory adjustments, as well as economic expansion. On the other hand, less financial stability is linked to bigger banks, greater financing risk, higher credit risk, and greater bank concentration. Greater operational and risk management difficulties may be faced by larger banks, and financial stability may be undermined by excessive funding and credit risk. The findings highlight the intricate relationships at work, where internal variables and external shocks like the COVID-19 epidemic combine to influence banks’ financial health. Policymakers and bank managers, who have to deal with the difficulties of controlling credit risk, interest rates, and bank size, need to know these insights. According to the study, resilience can be strengthened by prior financial stability and favorable economic indicators, but in order to maintain financial stability in the post-pandemic age, care must be taken to reduce the risks associated with larger banks and credit risk to ensure sustained financial stability in a post-pandemic era.